Quality of service in a public technological higher institute - Mundaca Constantino, Grimaldina (2022)
Public higher technological institutes (ITS) are of great importance in the training of technicians that companies demand, however, the State has been making an effort to raise quality standards in education, of course this situation basically generates discontent among teachers, because they have to adapt to a new way of teaching and apply technology in the teaching of their subjects, while the students have an opposite opinion. In this sense, the research was carried out by obtaining 109 data as a sample, in the same way after the bibliographic review it was concluded that there was no instrument applicable to this type of organizations, which is why a questionnaire was constructed, it was submitted to the KMO test, peer evaluation and reliability, for later application. The results showed that the institute effectively has old infrastructure, a lack of equipment and technology, there is no dissemination of technical careers in the demanding market, there is a lack of attention from teachers in the teaching-learning and tutoring processes, on the other hand, research is not carried out due to lack of resources, finally the institutional image is good for both society and companies.